WIPP documents available to the public (Raton, New Mexico Raton Range, 1991)
The Arthur Johnson Memorial Library has reports from the DOE, the State of New Mexico and various other groups perusal.
Newspaper article on Wipp documents at the library.
Master list item # 75
File location is in the Raton File Cabinet drawer 3
Keywords: Raton, New Mexico; Raton, New Mexico